Stress Field Distribution in Magnetoelastic Pressure Force Sensor - Iveta Tomcikova; Dobroslav Kovac; Irena Kovacova (Communications - Scientific letters of the University of Zilina, 2010)
Modelling of the stress field distribution in a magnetoelastic sensor core is proposed. The components of stress field are carried out by a numerical solution of boundary–value problem for stress field. The obtained results are presented in graphical form.